Factors associated with malnutrition in adolescent and adult patients with cystic fibrosis - Gabriela Cristofoli Barni; Gabriele Carra Forte; Luis Felipe Forgiarini; Claudine Lacerda de Oliveira Abrahão; Paulo de Tarso Roth Dalcin (Jornal Brasileiro de Pneumologia, 2017)
ABSTRACT Objective: To determine the prevalence of malnutrition in patients attending an adult cystic fibrosis (CF) program and to investigate the associations of malnutrition with the clinical characteristics of those patients. Methods: This was a cross-sectional study involving patients with clinically stable CF patients (16 years of age or older). The patients underwent clinical assessment, nutritional assessments, pulmonary function tests, and pancreatic function assessment. They also completed a questionnaire regarding diet compliance. On the basis of their nutritional status, the patients were classified divided into three groups: adequate nutrition; at nutritional risk; and malnutrition. Results: The study has included 73 patients (mean age, 25.6 ± 7.3 years), 40 of whom (54.8%) were female. The mean body mass index was 21.0 ± 3.0 kg/m2 and the mean FEV1 was 59.7 ± 30.6% of predicted. In this sample of patients, 32 (43.8%), 23 (31.5%), and 18 (24.7%) of the patients were allocated to the adequate nutrition, nutritional risk, and malnutrition groups, respectively. The logistic regression analysis identified three independent factors associated with the risk of malnutrition: Shwachman-Kulczycki score, percent predicted FEV1; and age. Conclusions: Malnutrition remains a common complication in adolescents and adults with CF, despite dietary advice. Malnutrition is associated with age, clinical severity, and lung function impairment.